Prevalence and Timing of Diagnosable Mental Health, Alcohol, and Substance Use Problems among Older Adolescents in the Child Welfare System - Keller, Thomas E. (2010)
This study reports the prevalence of PTSD, major depression, alcohol abuse/dependence and substance abuse/dependence diagnoses assessed with a structured clinical interview protocol in a population-based, multi-state, age cohort of older adolescents about to exit child welfare systems. PTSD was the most common diagnosis and was observed at rates above those seen in the general population. Rates of specific diagnoses varied according to gender, race, type of child welfare placement, and state of residence. In general, African American youth and those in kinship family foster care were less likely to have mental health and substance use problems. Analysis of the timing of onset relative to entry into care revealed that Caucasian youth were more likely to have diagnoses prior to entry into state custody, and race differentials were less pronounced for diagnosis after placement in foster care. Observed state-to-state differences suggest that age of entry into care and the likelihood of pre-existing mental health and substance use conditions could be attributable to child welfare policies regarding screening and placement.